Dimsum Lele: High Protein Food Innovation for a Stunting-Free Generation in Panduman Village - Rusdiarti, Rusdiarti; Jannah, Miftahul; Fitriyah, Dina; Ayu, Dessya Putri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The issue of stunting remains a significant challenge in the field of nutrition, impacting the quality of human resources in Indonesia. In Panduman Village, located in Jelbuk District of Jember Regency, the prevalence rate of stunting is notably high at 18.46%. One contributing factor is the low consumption of animal protein and the limited nutritional knowledge among mothers of toddlers. To address this issue, a community service program was implemented, focusing on balanced nutrition education and training on how to prepare dim sum using catfish, which is a local ingredient rich in protein. This initiative involved 30 participants, including pregnant women, breastfeeding mothers, mothers of toddlers, and posyandu cadres. The program included nutritional education through lectures, discussions, and evaluations conducted via pre- and post-tests. Participants then had the opportunity to practice making catfish dim sum. The evaluation results indicated an increase in the average knowledge of participants, rising from 65.88 to 72.35. Additionally, participants expressed high enthusiasm for making dim sum.This program has proven effective in enhancing public understanding of the importance of a balanced diet and food diversification based on local animal protein sources. It positively contributes to efforts to prevent stunting. It is hoped that the continuation of this initiative will further improve the nutritional status of the community in Panduman Village.